DUAL CAREER COUPLES IN KOLKATA AND THEIR STRESSFUL WORK LIFE BALANCE - Rudra De, Jhilam (International Journal of Research -GRANTHAALAYAH, 2017)
Dual-career couples were exceptions to the norm in the 1960s, but on date it is difficult to assess the number of married career women in the work force. Previous researches suggest that, the problems of the working women, who are a significant part of a dual career couple, may include lack of flexibility in the workplace, male-trailing spouses, career versus relationship child bearing conflicts etc. The key for dual career couples is to establish a system to help them balance their career and personal activities. For each couple the dynamics are little different, depending on their personal situations. The main aim of this research is to study the level of stress to maintain work life balance of the dual career couples, where the female counterparts are working in the private health sector in Kolkata. Cronbach alpha was used as a reliability test. Independent sample t-tests were used to study the effect of gender and family structure on respondents’ satisfaction towards WLB. Nowadays, a career is not a mere need, but rather, a necessity. It is evident that an understanding, accommodating, and sympathetic approach to the management of dual career stress can improve organizational effectiveness by fostering continued employment and maximum performance among dual career couples.